Literature review of impact assessment studies of potential application to natural resource management research (some literature resources) - Spilsbury, M.J.; Poulsen, J. (International Center for Tropical Agriculture, 2001)
This note is part of an on-going effort to gain insights to impact assessment and research uptake literature of relevance to natural resource management-related research. It is provided more for the reference list than for the merit of the associated text that is still at an early stage. Many more references have been collected but have yet to be screened for their potential relevance.